Investigation of Heat-Treated Cultivation Medium for Mammalian Cells with near Infrared Spectroscopy. Issue 4 (August 2016) - Szabó, Éva; Párta, László; Zalai, Dénes; Gergely, Szilveszter; Salgó, András
A chemically defined medium powder for Chinese hamster ovary (CHO) cell cultivation was investigated regarding its response to heat treatments with different exposure times (1 hour, 7 hours and 13 hours) and temperatures (30 °C, 50 °C and 70 °C). The heat treatments were performed according to a design of experiments approach. Spectra of the control and the treated powders were collected to compare the sample groups using a dispersive and a Fourier transform (FT) near infrared (NIR) spectrometer. Multivariate data analysis including unsupervised classification as principal component analysis and supervised classification as soft independent modelling of class analogy was employed to identify the treatment-induced variations in the samples. Samples were separated according to the temperature set points of heat treatments and the control samples were successfully discriminated based on second-derivative NIR spectra. In order to evaluate the impact of the treatments on the growth rate of CHO cells, shake flask cultivation experiments were also performed. The viable cell density results showed that both treatment temperature and treatment duration were significant factors ( p = 0.05). Additionally, the sensitivity of change detection for medium powders was higher in the case of NIR and FT-NIR measurement and spectrum analysis compared to traditional shake flask cultivation.